Research in labor economics. Vol. 18 - Robst, S. W.; Polachek, John (Emerald, 2000)
This work carries seven papers that analyze the effect of government and corporate actions on individuals' labor market behavior and seven others from a November 1996 conference at Cornell University discuss new empirical research on employer training.
Keywords: Labor economics.; Labor supply -- United States.; elektronické knihy; electronic books